HUBUNGAN POLA ASUH PERMISIF DAN IKLIM SEKOLAH DENGAN PERILAKU BULLYING PADA SISWA MTs AL-HALIM SIPOGU - Meutia Sari (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This study aims to determine the relationship between permissive parenting and school climate with bullying behavior on students of MTs Al-Halim Sipogu. Subjects who become respondents in this study amounted to 40 people. Data were collected through a scale designed in this study and distributed to the subject of research.The data were then analyzed by using simple and multiple corelation techniques with the help of SPSS 17 for windows. The result of the analysis shows that there is a positive correlation between permissive parenting pattern and school climate with bullying behavior on students of MTs Al-Halim Sipogu. The value of determination coefficient is 0,639 or have correlation equal to 41,6%. The relationship between permissive parenting variables with bullying behavior is 0.393 or has a relationship of 15.5% and the coefficient determinasai school climate with bullying behavior of 0.501 or has a relationship of 40.9%. The conclusion of this research is that there is negative correlation between permissive parenting pattern and school climate with bullying behavior on students of MTs Al-Halim Sipogu with 41,6%.Keywords: Permissive parenting pattern, school climate, bullying behavior.